STRES KERJA PADA PEKERJA YANG TERPAPAR KEBISINGAN DI PT. SEMEN BOSOWA BANYUWANGI: Workplace Stress on Noise Exposed Workers At PT. Semen Bosowa Banyuwangi - ikhya ulum uddin; Shoa'im Hidayat (Journal of Community Mental Health and Public Policy, 2018)
ABSTRACT Psychological or mental problems is one of the health problems that often occur in workers in an industry. Noise is one of the factors that can affect job stress. Production worker of PT. Semen Bosowa Banyuwangi has the potential to experience work stress. Method: This research is an observational research with descriptive research design with crossectional approach. Sampling using total sampling method, with 49 respondents. The variables in this study are job stress, noise intensity, noise complaints and respondent characteristics. Results: Respondents were on average 30 years old with the youngest age of 19 years and the oldest was 40 years old. Most recent education is taken by the respondent is the level of Senior High School (SMA). Most of the respondents are married. The average respondent has been working for 3.5 years. Most workers are exposed to noise with an intensity of 85 - 90 dBA. There are 38.8% of workers who feel disturbed by the noise work environment. Working stress in the medium category has the highest proportion with a percentage of 51%. Discussion: Workers production PT. Semen Bosowa Banyuwangi mostly experience moderate work stress. Occurrence of work stress tends to increase in line with the increase in noise intensity. Workers who feel disturbed by the noise are mostly experiencing moderate work stress.